2011
DOI: 10.3168/jds.2010-3855
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lameness on the resting behavior and metabolic status of dairy cattle during the transition period in a freestall-housed dairy herd

Abstract: The objective of this observational study was to examine the effect of lameness on the resting behavior of dairy cattle through the transition period in a mattress-bedded commercial freestall facility, and explore the relationships between lameness, behavior, and metabolic indicators of disease. A convenience sample was used, comprised of 40 multiparous and 17 primiparous Holstein cows that were recruited as they entered the close-up pen and tracked through the maternity, hospital, and fresh pens. At recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 35 publications
6
43
3
3
Order By: Relevance
“…A desirable correlation between milk BHBA and the overall score for feet and legs was also found, which is in agreement with earlier phenotypic studies examining lameness. Calderon and Cook (2011) found that moderate and severely lame cows had a significantly higher blood BHBA concentration than slightly lame or nonlame cows. Similar, Suthar et al (2013) reported that a postpartum blood BHBA threshold of ≥1.1 mmol/L increased the odds for lameness in dairy cows 1.8 times.…”
Section: Correlations Between Ebv For Milk Bhba and Routinely Evaluatmentioning
confidence: 94%
“…A desirable correlation between milk BHBA and the overall score for feet and legs was also found, which is in agreement with earlier phenotypic studies examining lameness. Calderon and Cook (2011) found that moderate and severely lame cows had a significantly higher blood BHBA concentration than slightly lame or nonlame cows. Similar, Suthar et al (2013) reported that a postpartum blood BHBA threshold of ≥1.1 mmol/L increased the odds for lameness in dairy cows 1.8 times.…”
Section: Correlations Between Ebv For Milk Bhba and Routinely Evaluatmentioning
confidence: 94%
“…Lameness frequently occurs within 60 d after calving (Booth et al, 2004), as the periparturient hormones and nutritional allocations shift and hooves become more susceptible to disease. Indirect problems such as reduced intake, lower milk yield, or reduced conception rates can arise as a consequence of subclinical or clinical lameness (Calderon and Cook, 2011;Alawneh et al, 2012a). Remedies already viewed as good dairy practice include the use of foot baths for infectious conditions, frequent hoof trimming, reducing damp environments, properly fitted stalls, and earlier recognition of problems with the use of technology such as accelerometers (Main et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The most common diseases seen in dairy cows are lameness and mastitis, and much is already known about the response of individual cows to clinical treatments for these conditions and the behaviour of sick animals. For example, it is known that the time spent lying down and the number of lying bouts increases when lame cows are compared with non-lame cows (Calderon and Cook, 2011;Navarro et al, 2013). In cows with mastitis, sickness is associated with a reduced lying time, an increased number of steps taken (more walking, less lying), and an increased rate of kicking during milking (Fogsgaard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%